UPAYA PEMULIHAN HAK KONSUMEN ATAS KERUGIAN PEMBELI TIKET KONSER COLDPLAY DARI PERSPEKTIF HUKUM PERLINDUNGAN KONSUMEN DAN PERATURAN TERKAIT: Efforts to Restore Consumer Rights for Losses of Coldplay Ticket Buyers from Perspective Consumer Protection Law and Relevant - Muhammad Raldo Johansyah; Anna Maria Tri Anggraini (Faculty of Law, Universitas Trisakti, 2025)
The phenomenon of high demand for music concert tickets in Indonesia raises various challenges, including problems in the electronic ticket sales system. The Coldplay concert in Jakarta in 2023 faced various consumer complaints related to ticket duplication, audience mobility issues, and security. The writing of this article aims the problem to examine the responsibilities of Coldplay concert promoters based on Law Number 8 of 1999 on Consumer Protection and Jakarta Governor’s Regulation No. 18 of 2019. The writing of this article uses a normative juridical method with a legislative and case study approach. The results of the discussion and the conclusion of this article suggest that violations of consumer rights occur as a result of promoters’ negligence in meeting consumer protection standards, giving rise to claims for damages. Recovery of consumer rights can be done through both litigation and non-litigation mechanisms. Therefore, there is a need for strengthening regulation and strict supervision in the entertainment industry to guarantee legal certainty for consumers.